Practice of physical exercise at the middle and third age: a comparative study of levels of functional capacity in localized and non-practicing gymnasts - Romano, Taís Alves (2018)
Introduction: Aging is a process that occurs naturally from birth to death and is characterized by a series of changes, among them, the decrease in functional capacity as a consequence of the decline of some components of physical capacity. Objective: To compare the level of functional capacity in middle-aged and elderly, practicing gymnastics and non-practicing. Materials and Methods: Participants were 60 people (30 practitioners of localized gymnastics and 30 non-practitioners) aged 45 to 80, of both sexes, in the city of Ubá-MG. As a data collection procedure, the International Physical Activity Questionnaire, in its short version, and used the self-perception scale of performance in Daily Life Activities, which evaluates the functional capacity. Results: In the group of practicing gymnasts, 15 were very active (50.0%) and 15, active (50.0%). In the group of non-practitioners, 6 were classified as very active (20.0%), 20 as active (66.7%) and 4 as insufficiently active B (13.3%). In both groups, the evaluated ones were classified with good and very good levels of functional capacity. However, a significantly higher mean (p <0.05) of functional capacity was found among those practicing gymnastics (151,70 ± 13,58), compared to non-practitioners (144.50 ± 16.00). Conclusion: Practitioners of localized gymnastics presented higher average levels of functional capacity than non-practitioners.